2013
DOI: 10.1152/ajplung.00058.2013
|View full text |Cite
|
Sign up to set email alerts
|

Lipoxin A4-mediated KATP potassium channel activation results in cystic fibrosis airway epithelial repair

Abstract: Buchanan PJ, McNally P, Harvey BJ, Urbach V. Lipoxin A4-mediated K ATP potassium channel activation results in cystic fibrosis airway epithelial repair. Am J Physiol Lung Cell Mol Physiol 305: L193-L201, 2013. First published May 17, 2013 doi:10.1152/ajplung.00058.2013The main cause of morbidity and mortality in cystic fibrosis (CF) is progressive lung destruction as a result of persistent bacterial infection and inflammation, coupled with reduced capacity for epithelial repair. Levels of the anti-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 51 publications
3
42
1
1
Order By: Relevance
“…It was shown that LXA 4 triggered an increase in migration, proliferation, and wound repair of both non-CF and CF airway epithelia. 215 The fact that these responses were completely abolished by FPR2/ALXR antagonists and FPR2/ ALXR siRNA suggests that providing FPR2/ALXR agonists to CF patients might be a potential therapeutic approach.…”
Section: Therapeutic Impactmentioning
confidence: 99%
“…It was shown that LXA 4 triggered an increase in migration, proliferation, and wound repair of both non-CF and CF airway epithelia. 215 The fact that these responses were completely abolished by FPR2/ALXR antagonists and FPR2/ ALXR siRNA suggests that providing FPR2/ALXR agonists to CF patients might be a potential therapeutic approach.…”
Section: Therapeutic Impactmentioning
confidence: 99%
“…In the present studies, Buchanan et al (10) show that LXA 4 increases cell proliferation and migration and wound healing in CF airway cultures and stimulates ATPactivated potassium (K ATP ) currents to enhance epithelial repair (10). They suggest that this anti-inflammatory response attenuation would be therapeutic in helping to block the lung damage and thereby stabilize lung function (10).…”
Section: Therapiesmentioning
confidence: 70%
“…There is a cumulative damage to the lungs in CF over time because of the chronic bacterial infections and continuous inflammatory responses (10). To test whether epithelial repair could be stimulated with an anti-inflammatory mediator, Buchanan et al (10) tested whether lipoxin A 4 (LXA 4 ), an eicosanoid formed from arachidonic acid, is beneficial in CF by suppressing the inflammatory damage to the lungs.…”
Section: Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipoxins have been shown to promote the activity and/or expression of many different types of ion channels including epithelial Na + channels, cystic fibrosis transmembrane conductance regulators, ATP-sensitive K + channels, Ca 2+ -activated anion channels, pannexin 1 hemichannels, and canonical subtype of TRP channels (TRPCs). These effects lead to beneficial outcomes with respect to fluid secretion in the airway (Pang et al, 2011; Verriere et al, 2012; Buchanan et al, 2013; Wang et al, 2013; Yang et al, 2013; Al-Alawi et al, 2014; Higgins et al, 2014, 2015; Qi et al, 2015). Recent studies showing similarly beneficial effects from treatment of other n−3 type pro-resolvents have also emerged in the airway field (Hiram et al, 2014; Wang et al, 2014; Colby et al, 2016).…”
Section: Fatty Acid-derived Pro-resolventsmentioning
confidence: 99%